Parental Experiences of Infant Car Bed Use After Failure of Car Seat Tolerance Screen. (25th December 2021) - O'Connor, Christina M.; McGrath, Jacqueline; DeGrazia, Michele
Abstract : Background: Failure of the car seat tolerance screen (CSTS) during hospitalization often leads to a recommendation for automobile travel within a car bed at discharge. Purpose: To describe the parental experience utilizing a car bed for infant automobile transportation. Methods: A descriptive, qualitative study design was undertaken with a purposive sample of parents recruited for a single interview in the pulmonary clinic at the time of the follow-up CSTS, approximately 1 month after hospital discharge. Interviews, guided by a semistructured interview tool, provided a holistic understanding of the parental experience utilizing car bed travel. Findings/Results: Data from 15 parental interviews revealed an overarching emotional journey consisting of 5 themes: (1) an adjustment period; (2) decision-making related to the car bed purchase; (3) encounters with varied provider education and knowledge; (4) safety and security of the car bed during transit; and (5) space and mobility restrictions imposed by the car bed. Implications for Practice: While recommendations exist for infant travel in a car seat, supportive recommendations for parents with an infant who needs to travel in a car bed do not exist. Based on study findings, providing parents supportive guidelines, education, and recommendations for their infant requiring travel in a car bed may be a strategy to ease the stress experienced in this situation. Implications for Research: Findings indicated a need to develop policies and standards, as well as comprehensive education, for providers and parents related to car bed travel. Further research is needed to identify strategies to best support parents and infants.